Speed‐of‐Processing Training in Assisted and Independent Living: A Randomized Controlled Trial. Issue 8 (4th July 2018) - Smith, Marianne; Jones, Michael P.; Dotson, Megan M.; Wolinsky, Fredric D.
Abstract : Objectives: To examine speed‐of‐processing training (SOPT) in older adults in senior living communities, especially those in assisted living. Design: Two‐arm, parallel, randomized controlled trial. Setting: Assisted and independent residence settings in 31 senior living communities. Participants: Individuals aged 55 to 102 (mean 81.0, 73.8% female, 76.4% living alone, 47.0% residing in assisted living; N=351). Intervention: The intervention was 10 hours of computerized SOPT at baseline with 4‐hour boosters at 5 and 11 months; the attention control was 10 hours of solving computerized crossword puzzles at baseline with 4‐hour boosters at 5 and 11 months. Measures: Outcomes were useful field of view (UFOV) scores and improvements of 0.5 standard deviations (SDs) or more (> 158.4 ms). Data collection occurred at baseline, after training, and 6 and 12 months. Random‐effects linear mixed‐effect models were used to estimate SOPT effects in intention‐to‐treat complete‐case and multiple imputation analyses. Results: We found statistically significantly small standardized effect sizes (Cohen's ds 0.25–0.40) for SOPT, reflecting processing speed improvements on UFOV scores (of 39–63 ms) and greater percentages (9.8 to 14.9 percentage point advantages) for achieving more than 0.5 SD improvements (> 158.4 ms) over the 3 time periods. Conclusion: These findings support public health messaging about the potential benefits of SOPT for older adults in senior living communities and support the feasibility and acceptability of SOPT in assisted and independent living for older adults.